Longitudinal Changes of Caudate-Based Resting State Functional Connectivity in Mild Traumatic Brain Injury - Xu, Hui; Wang, Xiaocui; Chen, Zhen; Bai, Guanghui; Yin, Bo; Wang, Shan; Sun, Chuanzhu; Gan, Shuoqiu; Wang, Zhuonan; Cao, Jieli; Niu, Xuan; Shao, Meihua; et al. (Frontiers in Neurology, 2018)
Mild traumatic brain injury is associated with dysfunctional brain network and accumulating evidence is pointing to the caudate as a vulnerable hub region. However, little is known about the longitudinal changes in the caudate-based resting-state functional connectivity following mild traumatic brain injury. In the current study, 50 patients with mild traumatic brain injury received resting-state functional magnetic resonance imaging as well as neuropsychological assessments within seven days post-injury (acute phase) and one month later (subacute phase). 36 age- and gender- matched healthy controls underwent the same protocol. The caudate was segmented into the dorsal and ventral sub-regions based on their related functionally distinct neural circuits and separate functional connectivity was investigated. Results indicated that patients with mild traumatic brain injury at acute phase exhibited reduced left dorsal caudate-based functional connectivity with ventral lateral prefrontal cortex, dorsal anterior cingulate cortex, and inferior parietal lobule, which mainly distributed in the cognitive control network, and reduced right ventral caudate-based functional connectivity with the dorsal lateral prefrontal cortex, dorsal anterior cingulate cortex and bilateral ventral anterior cingulate cortex, which mainly distributed in the executive network and emotional processing network. Furthermore, patients with mild traumatic brain injury presented the reduced functional connectivity between the left dorsal caudate and the ventral lateral prefrontal cortex compared with healthy controls at acute phase while this difference became no significance and return to the normal level following 1 month post-injury subacute phase. Similarly, the functional connectivity between the right ventral caudate and anterior cingulate cortex (both dorsal and ventral part) showed the reduced strength in patients compared with healthy controls only at the acute phase but presented no significant difference at subacute phase following mild TBI. Along the same line, patients with mild traumatic brain injury presented the impaired performance on the information processing speed and more complaints on the pain impact index at acute phase compared with healthy controls but showed no significant difference at the follow-up 1 month post-injury subacute phase. The longitudinal changes of caudate-based dysfunction connectivity could serve as a neuroimaging biomarker following patients with mild TBI.